The Impact of Butterfly Pea Flower (Clitoria ternatea L.) Extract on Atherosclerosis Biomarker Profiles in Obese White Rats (Rattus norvegicus L.) - Harefa, Karnirius; Ritonga, Ahmad Hafizullah; Aritonang, Barita; Gurusinga, Rahmad; Wulan, Sri; Irmayani, Irmayani (Journal of Biomedicine and Translational Research, 2024)
Background: Clitoria ternatea L., commonly known as butterfly pea flower, has gained attention as a potential agent in the prevention and treatment of atherosclerosis due to its rich content of bioactive compounds, such as anthocyanin, a type of flavonoid renowned for its potent antioxidant and anti-inflammatory properties, along with its ability to enhance the immune system.Objective: This study aimed to elucidate the positive impact of butterfly pea flower extract on atherosclerosis biomarker profiles.Methods: The approach framework used in this research is a true experimental laboratory with a Control Group Post-Test design. Obese male white rats were selected as the research subjects. Thirty-six obese white rats were randomly divided into six groups using the Completely Randomized Design (CRD) method. The data collected were VCAM and IL-6 levels from the blood serum of obese white rats tested using an ELISA photometer. The tunica intima thickness was measured using a microscope. Data were analyzed employing SPSS 18 software, utilizing one-way ANOVA statistical tests and post hoc Tukey tests.Results: The research showed that with the increase in Butterfly Flower Extract (BPFE) dose, there was a consistently lower level of inflammatory biomarkers, such as VCAM-1 and IL-6, compared to positive controls and other variations, as well as tunica intima thickness was thinning than others. A dose of 600 mg/kg BW (P3 group) had VCAM-1 levels up to 30.40 ± 6.71 ng/mL, IL-6 levels up to 17.70 ± 8.29 ng/mL, and tunica intima thickness up to 3.18 ± 1.24 µm.Conclusion: BPFE effectively lowers inflammatory biomarkers and thins the tunica intima thickness in obese white rats at 600 mg/kg BW dose. It may offer promising therapeutic potential in addressing atherosclerosis.